2018
DOI: 10.3892/ijo.2018.4298
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene modulates the suppression of multidrug resistance protein�1 and triggers autophagic and apoptotic mechanisms in cisplatin-resistant human oral cancer CAR cells via AKT signaling

Abstract: Pterostilbene is a natural polyphenolic compound that is primarily found in fruits, such as blueberries and has a similar structure to resveratrol. Pterostilbene exhibits antioxidant, anti-inflammatory and antitumor activity but the effects of pterostilbene on drug-resistant oral cancer cells and its underlying mechanisms of action have not yet been explored. Therefore, the present study was performed to clarify the anticancer effects of pterostilbene on cisplatin-resistant human oral cancer CAR cells. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 63 publications
0
41
0
1
Order By: Relevance
“…Induction of tumor cell apoptosis is one of the best strategies for treating glioma and multiple types of cancers (27,28). Apoptotic death can be activated by three main pathways (17,29). The extrinsic pathway is triggered through binding of extrinsic signals to death receptors, which leads to activation of caspase-8 (29,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of tumor cell apoptosis is one of the best strategies for treating glioma and multiple types of cancers (27,28). Apoptotic death can be activated by three main pathways (17,29). The extrinsic pathway is triggered through binding of extrinsic signals to death receptors, which leads to activation of caspase-8 (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…C6 cells (5x10 6 cells/75T flask) were incubated with the presence and absence of 0, 50, 100 and 200 µM of GdCl 3 for 24 h. After cells were lysed, total protein (40 µg) was separated using 10% SDS-polyacrylamide gel electrophoresis (PAGE) and transferred onto polyvinylidene difluoride (PVDF) membranes (Immobilon-P Transfer membrane; Merck Millipore, Darmstadt, Germany). As previously described (17,18), the membranes were probed with primary antibodies against caspase-3, caspase-8, caspase-9, cytochrome c, Bax, Bcl-2, p-ERK, ERK, p-JNK, JNK, p-p38, p38, (all 1:1,000 dilution) and β-actin (1:5,000 dilution). The membranes were then incubated with goat anti-rabbit IgG-HRP or goat anti-mouse IgG-HRP linked antibodies (1:10,000 dilution) for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…12,13,14 Bununla birlikte, güncel tedaviler kapsamında, kematerapötik ajanlara gelişen direnci aşmak ve yine bu ajanlara bağlı yan etkileri azaltmak için kombine ilaç tedavisi ve adjuvan tedavi yöntemlerinin geliştirilmesi de bulunmaktadır. 15 Gerek güncel tedavilerin geliştirilmesine, gerekse de kullanımda olan ve yeni geliştirilen ilaçların denenmesine yönelik hastalık modellerinin oluşturulması çok değerlidir. Bu nedenle çalışmamızın amacı, hastalık tedavisine destek sağlayacak ksenograft oral YHK fare modelinin geliştirilmesi olmuştur.…”
Section: Tepeklinikunclassified
“…Previous studies have found that natural products and phytochemicals in plants have certain curative effects on various types of cancers, including anticancer activity and low toxicity. Pterostilbene (PTE), a natural polyphenolic compound, primarily found in fruits, such as blueberries, grapes, and tree wood, 6) has received a great deal of attention for its potent antioxidant and anti-inflammatory properties 7) ; and anticancer effect on a wide range of cancers, including prostate, bladder, colorectal, and oral cancer and so on. 8) But the molecular mechanism is still unclear.…”
Section: Introductionmentioning
confidence: 99%